algebra
posted by Sab .
Rearrange r+s/8s=rs/8n to make r the subject.
OK, I have started by rearranging the formula:
8n(r+s)=8s(rs)
What do I do next?

so you must have meant
(r+s)/(8s)=(rs)/(8n)
so 8n(r+s)=8s(rs) is correct so far. Le'ts expand it
8nr + 8rs = 8rs  8s^2
8nr = 8s^2
nr = s^2
r = s^2/n 
thank you!

just realised, should the second line be
8nr+8NS?, not 8rs? 
just realised, should the second line be
8nr+8NS?, not 8rs?......... 
your are right, good for you to notice
I have to mind my n, r and s's
8nr + 8ns = 8rs  8s^2
collect all terms containing r to one side
8nr  8rs = 8s^2  8ns
factor out the r
r(8n  8s) = 8s^2  8ns
r = (8s^2  8ns)/(8n  8s)
divide top and bottom by 8 on the RS
r = (s^2  ns)/(ns)
or s(s+n)/(ns) 
great, that makes sense, thanks